2006
DOI: 10.1063/1.2387172
|View full text |Cite
|
Sign up to set email alerts
|

An improved collision efficiency model for particle aggregation

Abstract: A generalized geometric model is presented which describes the collision efficiency factor of aggregation ͑the probability of a binary particle or aggregate collision resulting in adhesion͒ for systems comprised of two oppositely charged species. Application of the general model to specific systems requires calculation of the area of each species available for collision with a second species. This is in contrast to previous models developed for polymer-particle flocculation that are based on the fractional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This is in agreement with the collision efficiency model presented by Olsen et al 2 However, Puertas et al found that if the surface potential of one species is lower than that of the other, a greater relative fraction of the less charged species is required to achieve the maximum aggregation rate. This change in optimum dosage should be due to a change in collision efficiency factor but the geometric model 2 of E makes no allowances for variation in surface potential.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is in agreement with the collision efficiency model presented by Olsen et al 2 However, Puertas et al found that if the surface potential of one species is lower than that of the other, a greater relative fraction of the less charged species is required to achieve the maximum aggregation rate. This change in optimum dosage should be due to a change in collision efficiency factor but the geometric model 2 of E makes no allowances for variation in surface potential.…”
Section: Introductionsupporting
confidence: 76%
“…The work presented here attempts to modify the collision efficiency model presented previously 2 to allow for soft interactions, i.e., particle interactions for which the Debye length is significant relative to the particle size. Correction factors are incorporated to account for interactions at a finite distance from the surface of the interacting species, and a number of trends observed from experiment and literature are explained qualitatively using the modified model.…”
Section: Introductionmentioning
confidence: 99%
“…While the collision frequency is generally agreed upon in the literature, a multitude of modelling approaches were published for the collision efficiency over the past years [2,[31][32][33][34][35][36]. In the following sections suitable literature models for the calculation of collision frequencies and efficiencies are introduced.…”
Section: Evaluation Of Aggregation Frequenciesmentioning
confidence: 99%
“…property state space. The development of appropriate kernels is an area of ongoing research [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Eq. 4.1), which is described as reactivity, sticking probability, or flocculation efficiency (Smellie and La Mer 1958;Hogg 1999;Sandkühler et al 2005;Oolsen et al 2006;.…”
mentioning
confidence: 99%